TEACHER TALK IN EFL CLASSROOM: A SPEECH ACT PERSPECTIVE : (Descriptive Research at MA NU Bilingual Sidoarjo) - Rihza Galih Fathurrochman; Achmad Anang Darmawan (STKIP Al Hikmah Surabaya, 2021)
Stern (1983) defines a language is viewed as foreign language when (1) it is used only to travel abroad, communicate with the native speaker, and reading a foreign literature, and (2) usually learnt at formal educational environment because lacks of support from natural environment. Moreover, the character is really suit to describe the position of English in Indonesia. For the sake of student’s foreign language acquisition, teacher talk has an important position to be a good model of how the language is used and the input in the process of language acquisition. Therefore, the research is meant to answer two questions (1) types of teacher talk in the English as Foreign Language classroom, and (2) Why the teacher uses the certain type of teacher talk. In order to answer the question, observation and semi structured interview have been done to reveal the types of teacher’s utterance in the classroom. The data of the research are analysed using qualitative methods and the result is presented in paragraph. As result, a teacher in MA Bilingual Muslimat NU Sidoarjo uses the directive sentence mostly in the classroom, since she believes that encourage students to speak in English is very necessary for English as foreign language learner. The teacher also produce only 30,12% utterances in the classroom interactions, which she also believes that it is necessary to give students more opportunity to speak in the class in order to enhance their willingness to speak in English